Strategic Development of the Arctic Region in the Context of Great Challenges and Threats - Tsvetkov, Valery A.; Dudin, Mikhail N.; Yuryeva, Anna A. (Economy of Regions, 2020)
The paper examines the possible concepts for developing the potential of the Russian Arctic that can be used for elaborating the regional development strategy. The research aims to analyse the opportunities and limitations of environmentally friendly, socially and economically sustainable development of the Arctic region. The multidisciplinary research methodology includes analytical, statistical and econometric methods, as well as the method of scientific synthesis. The analysis is based on the source data obtained from public sources. The study results fully confirm the hypothesis and show that, for the development of the Russian Arctic, it is inadvisable to use only the resource-rental pattern. The findings demonstrate that, in near future, the Russian Arctic will not be able to develop the research, transport and tourism sectors due to the lack of efficient logistics, adequate infrastructure and stable telecommunications. Private investors are not interested in the Arctic region, while public investment in environmentally friendly, socially and economically sustainable development is minimal. In the context of limited budgetary resources, as well as the tasks that require immediate action (e. g. recovering from the COVID-19 pandemic), the optimal solution is to restructure the activities of two natural monopolies in the region (PJSC Rosneft Oil Company and PJSC Gazprom). The research results can be used for establishing a new development strategy of the Russian Arctic. Further research should focus on methods and approaches to using modern digital technologies in the region for enabling environmentally safe, socially responsible and economically sustainable development of the Russian Arctic.